Association between Lipid Profile and Vitamin D Level - Abbod, Lamiaa Saoud; Algabar, Fatima Amer Abd; Ahmed, Dhea Sadi (Journal for Research in Applied Sciences and Biotechnology, 2024)
Cardiovascular danger elements include fatness, high blood pressure, diabetes, and hyperglycemia, and dyslipidemia are all linked to vitamin D insufficiency aside from cardiovascular disease itself. The purpose of this analysis was to look at how children who were not obese related their lipid profiles to their vitamin D levels. The study, which involved 26 Iraqi patients, revealed that the lipid profile was affected by the vitamin D level. Correlation between Vitamin D3 and cholesterol showed asignificant at the 0.05 level (0.960), and between Triglyceride showed (0.857) significant at the 0.05 level.and in the VLDL, LDL, HDL also showed significant at the 0.05 level ( -0.915, -0.974, -0.971).